Multiplexed computations in retinal ganglion cells of a single type - Stéphane Deny (Nature Portfolio, 2017)
Retinal ganglion cell subtypes are traditionally thought to encode a single visual feature across the visual field to form a feature map. Here the authors show that fast OFF ganglion cells in fact respond to two visual features, either object position or speed, depending on the stimulus location.